QuillBot as an online tool: Students’ alternative in paraphrasing and rewriting of English writing - Fitria, Tira Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
QuillBot is an online application to paraphrase writing, avoid plagiarism, summarize long sentences and improve grammar to be more precise and look professional. The objective of this research is to review the QuillBot as an Artificial Intelligence (AI) tool system for students’ in paraphrasing and rewriting English writing both in the free and premium versions. This research applies descriptive qualitative. The data used is an English abstract article. The results show that QuillBot paraphrasing tools use several ways to paraphrase the text: 1) paraphrasing by using equations or synonyms, 2) paraphrasing by changing the form of the word, 3) paraphrasing by using active or passive sentences, and 4) paraphrasing by changing the order of words in sentences. This paraphrasing uses Standard Mode, which serves to balance changes to the text when users input them but still keeps them from changing the actual (original) meaning of the text, also making the result look more original. QuillBot is one of the paraphrasings and summarizing tools that can be used by students for rewriting any content based on a state-of-the-art AI system. This tool can be the students’ alternative which provides a solution by helping paraphrase when students do not have the idea to paraphrase English writing manually. However, a good knowledge of vocabulary and understanding of English grammar, of course, will help students or other users (s) both in using online or manual paraphrasing to be better or the best quality.